Formation of Biofilm by Tetragenococcus halophilus Benefited Stress Tolerance and Anti-biofilm Activity Against S. aureus and S. Typhimurium - Yao, Shangjie; Hao, Liying; Zhou, Rongqing; Jin, Yao; Huang, Jun; Wu, Chongde (Frontiers in Microbiology, 2022)
Tetragenococcus halophilus, a halophilic lactic acid bacterium (LAB), plays an important role in the production of high-salt fermented foods. Generally, formation of biofilm benefits the fitness of cells when faced with competitive and increasingly hostile fermented environments. In this work, the biofilm-forming capacity of T. halophilus was investigated. The results showed that the optimal conditions for biofilm formation by T. halophilus were at 3–9% salt content, 0–6% ethanol content, pH 7.0, 30°C, and on the surface of stainless steel. Confocal laser scanning microscopy (CLSM) analysis presented a dense and flat biofilm with a thickness of about 24 μm, and higher amounts of live cells were located near the surface of biofilm and more dead cells located at the bottom. Proteins, polysaccharides, extracellular-DNA (eDNA), and humic-like substances were all proved to take part in biofilm formation. Higher basic surface charge, greater hydrophilicity, and lower intracellular lactate dehydrogenase (LDH) activities were detected in T. halophilus grown in biofilms. Atomic force microscopy (AFM) imaging revealed that biofilm cultures of T. halophilus had stronger surface adhesion forces than planktonic cells. Cells in biofilm exhibited higher cell viability under acid stress, ethanol stress, heat stress, and oxidative stress. In addition, T. halophilus biofilms exhibited aggregation activity and anti-biofilm activity against Staphylococcus aureus and Salmonella Typhimurium. Results presented in the study may contribute to enhancing stress tolerance of T. halophilus and utilize their antagonistic activities against foodborne pathogens during the production of fermented foods.